2012
DOI: 10.1167/iovs.12-9963
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Expression in Retinal Pigment Epithelial ARPE-19 Cells in Response to Coculture with Activated T Cells

Abstract: RPE cells responded to exposure to T-cell-derived cytokines by upregulating expression of multiple chemokines related to microglial, T-cell, and monocyte chemotaxis and activation. This inflammatory stress response may have implications for immune homeostasis in the retina, and for the further understanding of inflammatory ocular diseases such as uveitis and AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 60 publications
5
59
1
2
Order By: Relevance
“…Interestingly, however, the cells stimulated with both IFNγ and TNFα showed a significantly higher level of HLA-G than any other sample, indicating that the two cytokines had a synergistic effect on gene expression. These results suggested that HLA-G could be important for RPE signalling in inflammation and were in accordance with microarray results previously performed in our group (data not shown) [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, however, the cells stimulated with both IFNγ and TNFα showed a significantly higher level of HLA-G than any other sample, indicating that the two cytokines had a synergistic effect on gene expression. These results suggested that HLA-G could be important for RPE signalling in inflammation and were in accordance with microarray results previously performed in our group (data not shown) [23].…”
Section: Discussionsupporting
confidence: 93%
“…As a model for inflammation, cells were stimulated with 100ng recombinant human interferon-gamma (IFNγ) and/or 20ng recombinant human Tumor necrosis factor-alpha (TNFα) per ml medium, for 24 hours (both from Research and Diagnostic systems, Minnesota, USA). The concentrations of cytokines were chosen on the background of a study previously performed in our group [23]. …”
Section: Cells and Culturementioning
confidence: 99%
“…Since the chemokine system is a pleiotropic system, the secreted chemokines by UM might not only attract monocytes but also in addition more T cells, which in turn creates a vicious cycle leading to a tumor-promoting inflammatory microenvironment. It seems likely that the ability of the UM cell lines to attract monocytes is specific to UM, since supernatant from RPE cells that have been stimulated with activated T cells and also secrete a number of chemokines 33 does not lead to an increased monocyte attraction (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can modulate microglia effector functions through the release of chemokine (C-X3-C motif) ligand 1 (CX3CL1). CX3CL1 is the only known member of the CX3C chemokine family, which is expressed by several retinal cell types, e.g., endothelial cells, stromal cells, 15 and RPE cells, 16 whereas its G protein-coupled receptor (CX3CR1) is mainly expressed by microglia in the retina. 17 MSCs are negative for the expression of CX3CR1, but express high levels of CX3CL1.…”
Section: Introductionmentioning
confidence: 99%